Genetic Variations in the Flanking Regions of miR-101-2 Are Associated with Increased Risk of Breast Cancer - Chen, Jiaping (Public Library of Science, 2014)
Genetic variants in human microRNA (miRNA) genes may alter mature miRNA processing and/or target selection, and likely contribute to cancer susceptibility and disease progression. Previous studies have suggested that miR-101 may play important roles in the development of cancer by regulating key tumor-associated genes. However, the role of single nucleotide polymorphisms (SNPs) of miR-101 in breast cancer susceptibility remains unclear. In this study, we genotyped 11 SNPs of the miR-101 genes (including miR-101-1 and miR-101-2) in a case-control study of 1064 breast cancer cases and 1073 cancer-free controls. The results revealed that rs462480 and rs1053872 in the flank regions of pre-miR-101-2 were significantly associated with increased risk of breast cancer (rs462480 AC/CC vs AA: adjusted OR = 1.182, 95% CI: 1.030–1.357, P = 0.017; rs1053872 CG/GG vs CC: adjusted OR = 1.179, 95% CI: 1.040–1.337, P = 0.010). However, the remaining 9 SNPs were not significantly associated with risk of breast cancer. Additionally, combined analysis of the two high-risk SNPs revealed that subjects carrying the variant genotypes of rs462480 and rs1053872 had increased risk of breast cancer in a dose-response manner (P (trend) = 0.002). Compared with individuals with “0–1” risk allele, those carrying “2–4” risk alleles had 1.29-fold risk of breast cancer. In conclusion, these findings suggested that the SNPs rs462480 and rs1053872 residing in miR-101-2 gene may have a solid impact on genetic susceptibility to breast cancer, which may improve our understanding of the potential contribution of miRNA SNPs to cancer pathogenesis.